Polymer additive, flame retardant, polymer molding material and preparation method and application thereof

By using polymer additives with specific compositions and crystal structures, the problem of excessive molding shrinkage in aluminum diethylphosphinate in modified polymer composites was solved, resulting in lower molding shrinkage and better dimensional stability.

CN119307007AActive Publication Date: 2025-01-14SHANGHAI KINGFA SCI & TECH +2

Patent Information

Application Number
CN202411875707.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-01-14
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

Existing aluminum diethylphosphonate flame retardants have the problem of excessive molding shrinkage in modified polymer composites, especially in the field of precision injection molded parts, and existing technologies have not been able to effectively solve this problem.

Method used

Polymer additives with specific compositions and crystal structures, including aluminum diethylphosphinate and aluminum ethylbutylphosphinate, were used to determine their specific enthalpy ratio ΔH and peak temperatures T1, T2, and T3 by differential scanning calorimetry (DSC). The reaction conditions were controlled during the preparation process to obtain additives with lower molding shrinkage.

Benefits of technology

Lower molding shrinkage was achieved in polymer molding materials, improving the dimensional stability and molding accuracy of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The invention discloses a polymer additive, a flame retardant, a polymer molding material and a preparation method and application thereof. The polymer additive is prepared from aluminum diethyl phosphinate and aluminum ethyl butyl phosphinate; the polymer additive satisfies a double enthalpy ratio [Delta] H defined by the following formula (1): 0.90 < = [Delta] H < = 1.05; 135 DEG C < = T1 < = 160 DEG C, 165 DEG C < = T2 < = 185 DEG C, and 180 DEG C < = T3 < = 200 DEG C; formula (1): [Delta] H = (H2 + H3) / H1. The polymer additive provided by the invention has a specific crystal transformation state, and the polymer molding material added with the polymer additive has a lower molding shrinkage rate in a molding application process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of flame retardants, and more specifically, relates to a polymer additive, a flame retardant, a polymer molding material, and a preparation method and application thereof. Background Art

[0002] Aluminum diethylphosphinate is a halogen-free, green and environmentally friendly flame retardant. It appears as a white powder. It is insoluble in water and most organic solvents, but easily soluble in strong acid and strong alkali solutions. It has the characteristics of high efficiency flame retardancy, high thermal stability, low smoke, small particle size, low specific gravity, good dispersibility and compatibility. As an efficient, green and environmentally friendly halogen-free flame retardant, aluminum diethylphosphinate is widely used in flame retardant products such as thermoplastics (such as PA6T, PA10T, PA66, PBT), fibers and textiles.

[0003] The compound system of aluminum diethylphosphinate is widely used in the field of halogen-free flame-retardant glass fiber reinforced engineering plastics, such as the aluminum diethylphosphinate compounded with melamine polyphosphate (MPP) system, the aluminum diethylphosphinate compounded with melamine cyanuric acid (MCA) system, and the aluminum diethylphosphinate compounded with aluminum phosphite system. These systems have the advantages of high flame retardant efficiency, high temperature resistance, and low loss of resin matrix performance, and are therefore widely used.

[0004] In the application process of modified polymer composite materials such as diethyl aluminum phosphinate flame retardant modified thermoplastics, the molding shrinkage of the material is often too large, resulting in problems such as the inability to match the installation of the injection molded parts or loose assembly, especially in the field of some precision injection molded parts.

[0005] Patent CN110407869A discloses a monotrifluoropropyl phosphinate aluminum flame retardant, which uses monotrifluoropropyl phosphinate aluminum and diethyl phosphinate aluminum to reduce the corrosiveness of diethyl phosphinate aluminum to the screw during the extrusion modification process, but it does not improve the problem of excessive shrinkage of the modified polymer composite material. Patent CN113637193A discloses a nylon insulation strip or reinforced nylon, glass fiber reinforced PA6 / PA66 composite material, including nylon 6633, diethyl phosphinate aluminum, antioxidant, glass fiber, lubricant maleic anhydride grafted POE toughening agent and additives, and the nylon itself is enhanced by adding glass fiber, so that the water absorption of the composite material is reduced, and the product molding shrinkage is reduced, and the dimensional stability is improved. However, in this scheme, diethyl phosphinate aluminum is only used as a flame retardant component. During its application, diethyl phosphinate aluminum still causes the modified polymer composite material to have excessive shrinkage during molding. Summary of the invention

[0006] In view of the above-mentioned existing technical problems, the primary purpose of the present invention is to provide a polymer additive, which has a relatively special crystal morphology and crystalline structure, and has a lower molding shrinkage rate during the application process of the polymer as an additive.

[0007] In order to achieve the above object, the present invention is implemented by the following technical solutions: The present invention claims a polymer additive, comprising: aluminum diethylphosphinate and aluminum ethylbutylphosphinate; The polymer additive satisfies the double enthalpy ratio ΔH defined by the following formula (1): 0.90≤ΔH≤1.05; and satisfies 135°C≤T1≤160°C, 165°C≤T2≤185°C, 180°C≤T3≤200°C; Formula (1) ΔH = (H2 + H3) / H1; The polymer additive is tested by differential scanning calorimetry (DSC), and the testing method is as follows: in a nitrogen atmosphere, the polymer additive is heated from room temperature to a maximum temperature of 300°C at a heating rate of 20°C / min, and then cooled to room temperature at a rate of 20°C / min after staying at this temperature for 3 minutes, to obtain a cooling curve of the polymer additive; the polymer additive is kept at room temperature for 3 minutes, and then heated to a maximum temperature of 300°C at a heating rate of 20°C / min again, to obtain a second heating curve of the polymer additive; H1 is the peak area formed by the starting temperature and the ending temperature of the exothermic peak on the cooling curve; two endothermic peaks on the second heating curve are selected, and the temperature is from low to high, H2 is the peak area formed by the starting temperature and the ending temperature of the first endothermic peak on the second heating curve, and H3 is the peak area formed by the starting temperature and the ending temperature of the second endothermic peak on the second heating curve.

[0008] T1 is the peak temperature of the exothermic peak on the cooling curve, T2 is the peak temperature of the first endothermic peak on the second heating curve, and T3 is the peak temperature of the second endothermic peak on the second heating curve.

[0009] Differential scanning calorimetry (DSC) is one of the most commonly used thermal analysis instruments. It can be used to characterize the melting and crystallization process of materials, reflecting the relationship between molecular chain structure and crystallization. In addition, for some substances without melting phenomenon, obvious endothermic peaks and exothermic peaks will appear during the DSC test. The difference between the endothermic peak and the exothermic peak is also related to the change of molecular structure or its crystallization performance. The change of molecular structure or its crystal structure directly determines the melting or crystallization behavior of DSC during heating or cooling, as well as the difference between the endothermic peak and the exothermic peak. The difference in molecular structure of materials will also affect their processing fluidity and mechanical properties during processing, and thus affect the dimensional stability and molding shrinkage of the material.

[0010] The present invention has found through research that although the polymer additive provided by the present invention has no melting phenomenon during the test process at 30-300°C, the endothermic peaks and exothermic peaks of different polymer additives are significantly different. The inventors have found through research that the specific double enthalpy ratio formed in the endothermic peak and the exothermic peak, as well as the specific peak temperature (T1, T2, T3), affect the specific crystallization transition state of the polymer additive. This state gives the polymer molding material better dimensional stability during the polymer molding process, so the polymer molding material exhibits a smaller molding shrinkage. The polymer molding material prepared by using the polymer additive having this specific crystal transition state as an additive has a lower molding shrinkage.

[0011] In some embodiments, the peak areas H1, H2, H3 and peak positions T1, T2, T3 can be obtained by peak marking and integral calculation of peak areas using existing methods in the art, such as peak marking and integral calculation of peak areas using software provided in the DSC device. Specifically, in some embodiments, when using differential scanning calorimetry DSC for testing, the weight of the test sample of the polymer additive can be 10±0.5 mg.

[0012] Specifically, in some embodiments, the peak areas H1, H2, H3 and the peak positions T1, T2, T3 can be integrated or marked multiple times and then averaged and tested, such as once, twice, three times, four times, five times, etc. More specifically, from the perspective of saving operations and maintaining data reproducibility and reliability, the peak areas H1, H2, H3 and the peak positions T1, T2, T3 can be tested 2-4 times and averaged and obtained.

[0013] In some embodiments, the polymer additive includes, by weight percentage, 99.01-99.99% aluminum diethylphosphinate and 0.01-0.99% aluminum ethylbutylphosphinate. More specifically, the content of aluminum diethylphosphinate may be 99.10%, 99.20%, 99.30%, 99.40%, 99.50%, 99.60%, 99.70%, 99.80%, 99.90%, etc., or an interval range formed by any of the above values, such as 99.01-99.40%, 99.01-99.70%, 99.01-99.90%, 99.30-99.60%, 99.50-99.90%, 99.70-99.99%, 99.90-99.99%, etc., and the present invention is not limited thereto. More specifically, the content of ethylbutylphosphinate aluminum can be 0.03%, 0.05%, 0.08%, 0.10%, 0.20%, 0.30%, 0.40%, 0.50%, 0.60%, 0.70%, 0.80%, 0.90%, 0.93%, 0.95%, 0.97%, etc., or an interval range formed by any of the above values, such as 0.01-0.10%, 0.01-0.30%, 0.01-0.70%, 0.10-0.80%, 0.30-0.90%, 0.70-0.93%, 0.80-0.99%, 0.90-0.99%, etc., but the present invention is not limited thereto.

[0014] In some embodiments, aluminum diethylphosphinate and aluminum ethylbutylphosphinate may exist in a physical combination; in some embodiments, aluminum diethylphosphinate and aluminum ethylbutylphosphinate may exist in a chemical coprecipitation form of ions of formula I and formula II; in some embodiments, aluminum diethylphosphinate and aluminum ethylbutylphosphinate may exist in both a physical combination and a chemical coprecipitation form of ions of formula I and formula II.

[0015] .

[0016] More specifically, in the present invention, the double enthalpy ratio ΔH can be 0.92, 0.94, 0.96, 0.98, 0.99, 1.00, 1.02, 1.04, 1.05, etc., or an interval range formed by any of the above values, such as 0.92-0.98, 0.96-1.05, etc., but the present invention is not limited thereto.

[0017] More specifically, in the present invention, the T1 can be 135°C, 138°C, 140°C, 142°C, 144°C, 146°C, 148°C, 150°C, 152°C, 154°C, 156°C, 158°C, etc., or an interval range formed by any of the above values, such as 140°C to 150°C, 146°C to 154°C, etc., but the present invention is not limited thereto.

[0018] More specifically, in the present invention, the T2 can be 168°C, 170°C, 172°C, 174°C, 176°C, 178°C, 180°C, 183°C, etc., or an interval range formed by any of the above values, such as 174°C to 178°C, etc., but the present invention is not limited thereto.

[0019] More specifically, in the present invention, the T3 can be 182°C, 184°C, 186°C, 188°C, 190°C, 192°C, 194°C, 196°C, 198°C, etc., or an interval range formed by any of the above values, such as 184°C~188°C, 190°C~192°C, etc., but the present invention is not limited thereto.

[0020] In some embodiments, the polymer additive satisfies a double enthalpy ratio ΔH: 0.92≤ΔH≤1.05.

[0021] In some embodiments, the polymer additive satisfies 140°C≤T1≤156°C, 172°C≤T2≤178°C, and 184°C≤T3≤192°C.

[0022] In some embodiments, the present invention claims a method for preparing a polymer additive, comprising the steps of: S1. Under nitrogen protection, a water-soluble salt or acid of hypophosphorous acid, an initiator and an olefin are reacted, and 2.00 to 2.05 molecules of olefin are added relative to the P of each water-soluble salt or acid of hypophosphorous acid itself to obtain an aqueous intermediate solution containing diethylphosphinate; S2. The intermediate aqueous solution of step S1, the surfactant and the aluminum salt solution are reacted to obtain the polymer additive.

[0023] In the above embodiment, in step S1, the reaction temperature is 80-120°C.

[0024] In the above embodiment, in step S1, the reaction pressure is 0.6-2.0 MPa.

[0025] In the above embodiment, in step S1, insulation is carried out in two steps, the first insulation is heated to 80-90°C for 3.5-4.5 hours, and the initiator is continuously added during the insulation process; then the insulation is continued at 90-100°C for 0.5-1.5 hours; or insulation is carried out in two steps, the first insulation is heated to 105-115°C for 3.5-4.5 hours, and the initiator is continuously added during the insulation process; then the insulation is continued at 105-115°C for 0.5-1.5 hours.

[0026] In the above embodiment, in step S2, the mass concentration of diethylphosphinate in the intermediate aqueous solution is 15-25%; in step S2, the mass concentration of water-soluble aluminum salt in the aluminum salt solution is 20-24%.

[0027] In the above embodiment, in step S2, the surfactant is selected from one or more of alkyl phosphate esters, alkyl phosphate salts, ether alcohol phosphate esters, and ether alcohol phosphate salts.

[0028] Specifically, the alkyl phosphate or alkyl phosphate salt can be selected from alkyl phosphate or alkyl phosphate salts of 8 to 18 carbon atoms; more specifically, the alkyl phosphate includes but is not limited to monolauric acid phosphate, etc.; the alkyl phosphate salt includes but is not limited to monododecyl potassium phosphate, etc. Specifically, the ether alcohol phosphate or ether alcohol phosphate salt can be selected from ether alcohol phosphate or ether alcohol phosphate salts of 8 to 18 carbon atoms; more specifically, the ether alcohol phosphate includes but is not limited to lauryl ether phosphate, etc.; the ether alcohol phosphate salt includes but is not limited to lauryl potassium phosphate, etc.

[0029] In the above embodiment, the amount of the surfactant added is 0.001 to 0.10% by weight of the intermediate aqueous solution. More preferably, the amount of the surfactant added is 0.01 to 0.08% by weight of the intermediate aqueous solution.

[0030] In the above embodiment, before adding the surfactant, the intermediate aqueous solution is also neutralized by adding an alkali solution to remove the free acid in the solution system. More specifically, the pH is neutralized to 5 to 6.5.

[0031] In the above embodiment, in step S2, the intermediate aqueous solution and the aluminum salt solution are used in equal amounts.

[0032] In the above embodiment, the aluminum salt solution is added at one time, the temperature of the aluminum salt solution is raised to 50-60° C. during the addition process, and the addition time is controlled to be 90-110 min; and / or In step S2, aluminum salt solution is added twice. The first time, 15-35% equivalent aluminum salt solution is added, the addition time is controlled to be 30-40 minutes, and the temperature is controlled to be 35-45°C; the second time, 65-85% equivalent aluminum salt solution is added, the addition time is controlled to be 30-40 minutes, and the temperature is controlled to be 55-60°C.

[0033] In some embodiments, the present invention claims another method for preparing a polymer additive, comprising the following preparation steps: S1. Under nitrogen protection, an aqueous solution of hypophosphorous acid, an initiator and an olefin are reacted, and 2.00 to 2.05 molecules of olefin are added relative to the P of each hypophosphorous acid itself to obtain an aqueous intermediate solution containing diethylphosphinic acid; S2. Preparing an aluminum hydroxide gel solution; S3. Drop the intermediate aqueous solution of step S1 into the aluminum hydroxide gel solution of step S2 for reaction, raise the temperature to 50-60°C, keep the temperature for 0.1-0.5h; then raise the temperature to 90-120°C, keep the temperature for 0.5-5h, to obtain a polymer additive.

[0034] In the above embodiment, in step S1, insulation is performed in two steps. The temperature of the first insulation is 75-85°C and the time is 2.5-3.5 hours. The initiator is continuously added during the insulation process. During the insulation process, part of the reaction materials in the reactor are passed into the Venturi ejector and are fully mixed with the ethylene passed into the Venturi ejector, and then enter the reactor after external circulation. Then, insulation is continued for 0.5-1.5 hours.

[0035] In the above embodiment, in step S2, the reaction temperature of the preparation is 10-20°C.

[0036] In the above embodiment, in step S3, the temperature is raised to 50-60°C at a heating rate of 2-10°C / h; and / or In the above embodiment, in step S3, the temperature is increased to 90-120° C. at a heating rate of 11-25° C. / h.

[0037] In the above embodiment, in step S3, the molar ratio of diethylphosphinic acid to aluminum ions in the aluminum hydroxide gel solution is 3:1 to 1.01.

[0038] In some embodiments, the olefin may be at least one of ethylene, propylene, 1-butene, 2-butene, 1-pentene, 1-hexene, or 1-octene.

[0039] In some embodiments, the water-soluble salt of hypophosphorous acid may be potassium hypophosphite or sodium hypophosphite.

[0040] In some embodiments, the water-soluble aluminum salt may be an oxide, hydroxide, peroxide, sulfate, bisulfate, hydrated sulfate, persulfate, phosphate, and / or phosphite of aluminum.

[0041] In some embodiments, the initiator is selected from one or more of organic peroxides, inorganic peroxides, and azo compounds. More specifically, the inorganic peroxide may be one or more of sodium persulfate, ammonium persulfate, or potassium persulfate. The organic peroxide may be one or more of benzoic acid peroxide, lauric acid peroxide, di-tert-butyl peroxide, peroxycarbonate, acetic acid peroxide, tert-butyl peroxyisobutyrate, tert-butyl peroxypivalate, tert-butyl peroxy-2-ethylhexanoate, or tri-amyl peroxide; the azo compound may be one or more of azobisisobutyronitrile or azobisisoheptonitrile.

[0042] Furthermore, the present invention claims the use of the above polymer additive in reducing the shrinkage of a polymer.

[0043] Furthermore, the present invention claims the use of the above-mentioned polymer additives as reactive and / or non-reactive flame retardants for polymers, as flame retardants for varnishes and foam-type coatings, as flame retardants for wood and other cellulose-containing products, for the preparation of flame-retardant polymer molding materials, for the preparation of flame-retardant polymer moldings and / or for imparting flame retardancy to polyester and pure and blended cellulose fabrics by impregnation.

[0044] In some embodiments, the polymer additive is used with a synergist; the synergist is melamine phosphate, di(melamine) phosphate, penta(melamine) triphosphate, tri(melamine) diphosphate, tetra(melamine) triphosphate, hexa(melamine) pentaphosphate, diphosphate, tetraphosphate, melamine pyrophosphate, polyphosphate melamine, polyphosphate melam, polyphosphate melem and / or polyphosphate melon; is a melamine condensation product such as melam, melem and / or melon; is an oligoester of tri(hydroxyethyl) isocyanurate / salt and aromatic polycarboxylic acid, benzoguanamine, tri(hydroxyethyl) isocyanurate ... isocyanurate / salt of ethyl) isocyanurate / salt, allantoin, glycoluril, melamine, melamine cyanurate, urea cyanurate, dicyandiamide and / or guanidine; is a nitrogen-containing phosphate of the formula (NH4)yH3-yPO4 or (NH4PO3)z, wherein y is 1 to 3 and z is 1 to 10000; is aluminum phosphite, aluminum pyrophosphite; is zinc borate, zinc carbonate, zinc stannate, basic zinc stannate, zinc phosphate, zinc oxide, zinc hydroxide, tin oxide hydrate, basic zinc silicate, magnesium hydroxide, hydrotalcite, magnesium carbonate; is a salt of ethylphosphonic acid, a salt of butylphosphonic acid, a salt of n-butylphosphonic acid, a salt of sec-butylphosphonic acid and / or a salt of hexylphosphonic acid.

[0045] In some embodiments, the polymer additive is used with an additive selected from at least one of an antioxidant, a UV stabilizer, a gamma stabilizer, a hydrolysis stabilizer, an antistatic agent, an emulsifier, a nucleating agent, a softener, a processing aid, an impact modifier, a dye, or a pigment.

[0046] In some embodiments, 0.0001 to 99.7999 wt % of the polymer additive, 0.1 to 40 wt % of the synergist, and 0.1 to 40 wt % of the additive are used.

[0047] In some embodiments, the present invention claims flame retardant thermoplastic or thermosetting polymer molding materials, polymer moldings, polymer films, polymer filaments and / or polymer fibers, comprising: 0.5 to 45 wt % of the polymer additive, 0.5 to 95 wt % of a thermoplastic or thermosetting polymer or a mixture thereof, 0 to 55 wt % of a synergist and 0 to 55 wt % of a filler or reinforcing material.

[0048] In some embodiments, the polymer is selected from polyesters, polyamides, thermoplastic elastomers, thermoplastic polyurethanes, thermoplastic polyester elastomers, styrenic polymers, polyketones, polyolefins, polyacrylates, and / or polymer blends comprising polyamides or polyesters.

[0049] In some embodiments, the polyolefins may be polymers of monoolefins and dienes, such as polypropylene, polyisobutylene, poly-1-butene, poly-4-methyl-1-pentene, polyisoprene or polybutadiene, and polymers of cyclic olefins, such as cyclopentene or norbornene; furthermore polyethylenes (which may optionally be crosslinked), such as high-density polyethylene (HDPE), high-density and high-molar-mass polyethylene (HDPE-HMW), high-density and ultra-high-molar-mass polyethylene (HDPE-UHMW), medium-density polyethylene (MDPE), low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), branched low-density polyethylene (VLDPE) and mixtures thereof.

[0050] The polyolefin may also be a copolymer of a monoolefin and a diene with each other or with other vinyl monomers, for example, ethylene propylene copolymer, linear low density polyethylene (LLDPE) and its mixture with low density polyethylene (LDPE), propylene-1-butene copolymer, propylene-isobutylene copolymer, ethylene-1-butene copolymer, ethylene-hexene copolymer, ethylene-methylpentene copolymer, ethylene-heptene copolymer, ethylene-octene copolymer, propylene-butadiene copolymer, isobutylene-isoprene copolymer, ethylene-alkyl acrylate copolymer, ethylene-alkyl methylpropionate copolymer, ethylene-vinyl acetate copolymer. Polymers and their copolymers with carbon monoxide, or ethylene-acrylic acid copolymers and their salts (ionomers), and terpolymers of ethylene with propylene and a diene, such as hexadiene, dicyclopentadiene or ethylidene norbornene; furthermore mixtures of such copolymers with one another, for example polypropylene / ethylene-propylene copolymers, LDPE / ethylene-vinyl acetate copolymers, LDPE / ethylene-acrylic acid copolymers, LLDPE / ethylene-vinyl acetate copolymers, LLDPE / ethylene-acrylic acid copolymers and alternating or statistically constructed polyalkylene / carbon monoxide copolymers and mixtures thereof with other polymers, such as polyamides.

[0051] In some embodiments, the styrenic polymer can be a copolymer of styrene or α-methylstyrene with a diene or acrylic derivative, such as styrene-butadiene, styrene-acrylonitrile, styrene-alkyl methacrylate, styrene-butadiene-alkyl acrylate and styrene-butadiene-alkyl methacrylate, styrene-maleic anhydride, styrene-acrylonitrile-methyl acrylate; a high impact strength mixture from a styrene copolymer and another polymer such as a polyacrylate, a diene polymer or an ethylene-propylene-diene terpolymer; and block copolymers of styrene, such as styrene-butadiene-styrene, styrene-isoprene-styrene, styrene-ethylene / butylene-styrene or styrene-ethylene / propylene-styrene. In some embodiments, the styrenic polymer can be a graft copolymer of styrene or α-methylstyrene, such as styrene grafted on polybutadiene, styrene grafted on polybutadiene-styrene copolymer or polybutadiene-acrylonitrile copolymer, styrene and acrylonitrile (or methacrylonitrile) grafted on polybutadiene; styrene, acrylonitrile and methyl methacrylate grafted on polybutadiene; styrene and maleic anhydride grafted on polybutadiene; styrene, acrylonitrile and maleic anhydride or maleimide grafted on polybutadiene; styrene and maleimide grafted on polybutadiene, styrene and alkyl acrylate or alkyl methacrylate grafted on polybutadiene, styrene and acrylonitrile grafted on ethylene-propylene-diene terpolymer, styrene and acrylonitrile grafted on polyalkyl acrylate or polyalkyl methacrylate, styrene and acrylonitrile grafted on acrylate-butadiene copolymer, and mixtures thereof, such as ABS polymers, MBS polymers, ASA polymers, or AES polymers.

[0052] In some embodiments, the polyamide can be a polyamide and copolyamide derived from diamines and dicarboxylic acids and / or derived from aminocarboxylic acids or the corresponding lactams, such as PA6, PA66, PA46, etc.; an aromatic polyamide from meta-xylene, a diamine and adipic acid; a polyamide prepared from hexamethylenediamine and isophthalic acid and / or terephthalic acid and optionally an elastomer as a modifier (polyhexamethylene isophthalamide, polyhexamethylene terephthalamide), such as poly-2,4,4-trimethylhexamethylene terephthalamide or poly-m-phenylene isophthalamide; or a block copolymer of a polyamide with a polyolefin, an olefin copolymer, an ionomer or a chemically bonded or grafted elastomer; or a block copolymer with a polyether, such as polyethylene glycol, polypropylene glycol or polybutylene glycol.

[0053] In some embodiments, the polyester can be a polyester derived from a dicarboxylic acid and a diol and / or derived from a hydroxycarboxylic acid or the corresponding lactone, such as polyethylene terephthalate, polybutylene terephthalate, poly-1,4-dihydroxymethylcyclohexane terephthalate, polyhydroxybenzoates, and block polyetheresters derived from polyethers having hydroxyl end groups; and polyesters modified with polycarbonate or MBS.

[0054] In some embodiments, the filler or reinforcing material can be an oxygen-containing compound of silicon, a magnesium compound, such as a metal carbonate of a metal of the second main group of the periodic table, magnesium oxide, magnesium hydroxide, hydrotalcite, dihydrotalcite, magnesium carbonate or magnesium calcium carbonate; a calcium compound such as calcium hydroxide, calcium oxide, hydrocalumite, an aluminum compound such as aluminum oxide, aluminum hydroxide, boehmite, gibbsite or aluminum phosphate, red phosphorus, a zinc compound, or glass fiber.

[0055] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a polymer additive, which has specific ΔH, T1, T2 and T3. The polymer additive within the above-mentioned specific range has a specific crystal transition state, and a polymer molding material added with the polymer additive has a lower molding shrinkage rate during molding application. DETAILED DESCRIPTION

[0056] The present invention is further described below in conjunction with the specification and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0057] The raw materials used in the embodiments and comparative examples are described as follows: Fiberglass, ECS10-03-568H, Jushi Co., Ltd.

[0058] Base resin 1: PA66, EPR24, Henan Shenma.

[0059] Base resin 2: PBT, GX121, Yizheng Chemical.

[0060] Base resin 3: PA6, M2000, Guangdong Xinhui Meida.

[0061] Synergist 1: melamine polyphosphate, MPP, Budit 3141, Budenheim.

[0062] Synergist 2: Zinc borate, ZB-503, Anhui Yishitong Materials.

[0063] Synergist 3: aluminum phosphite, commercially available.

[0064] Sodium hypophosphite monohydrate, commercially available.

[0065] Sodium persulfate, commercially available.

[0066] Aluminum sulfate, commercially available.

[0067] Monolauryl phosphate, commercially available.

[0068] Lauryl ether phosphate, commercially available.

[0069] Potassium lauryl phosphate, commercially available.

[0070] Unless otherwise specified, the components used in the parallel embodiments and comparative examples are all the same commercially available products.

[0071] Example 1 A polymer additive (1) 318 g of solid sodium hypophosphite monohydrate, 400 g of water and 2 g of tert-butyl peroxy-2-ethylhexanoate were placed in an autoclave, the air in the autoclave was replaced with nitrogen for 5 times, ethylene was introduced into the autoclave, the ethylene pressure in the autoclave was made constant to 0.6 MPa through a pressure reducer, the autoclave was heated to 85°C and kept warm for 4 h, 4 g of tert-butyl peroxy-2-ethylhexanoate was continuously added during the 4 h of keeping warm, and then the autoclave was kept warm at 95°C for 1 h, cooled and vented to obtain an aqueous solution containing sodium diethylphosphinate.

[0072] (2) Add 20 wt % sodium hydroxide aqueous solution to the aqueous solution containing sodium diethylphosphinate obtained in step (1) to neutralize the free acid to pH=6, add water to dilute to a mass concentration of sodium diethylphosphinate of 20%, add 0.03 % (the amount added is calculated by the weight of the diluted sodium diethylphosphinate aqueous solution) of monolauric acid phosphate, and dropwise add 1 / 6 equivalent (calculated by molar amount of sodium diethylphosphinate) of a 20 % aluminum sulfate aqueous solution at 40°C for 40 minutes; raise the temperature to 55°C, dropwise add the remaining 5 / 6 equivalent (calculated by molar amount of sodium diethylphosphinate) of a 20 % aluminum sulfate aqueous solution for 40 minutes; then cool and filter in sequence, wash the filter cake three times with water of 3 times the weight of the filter cake, and then dry at 120°C to constant weight to obtain a polymer additive.

[0073] Example 2 A polymer additive (1) 318 g of solid sodium hypophosphite monohydrate, 400 g of water and 2 g of sodium persulfate were placed in an autoclave, the air in the autoclave was replaced with nitrogen for 5 times, ethylene was introduced into the autoclave, the ethylene pressure in the autoclave was kept constant at 1.5 MPa through a pressure reducer, the autoclave was heated to 110° C. and kept warm for 4 h. A solution prepared by 4 g of sodium persulfate and 36 g of water was continuously added during the 4 h heat preservation process, and then kept warm at 110° C. for 1 h, cooled and vented to obtain an aqueous solution containing sodium diethylphosphinate.

[0074] (2) The aqueous solution containing sodium diethylphosphinate obtained in step (1) is added with 20wt% sodium hydroxide aqueous solution to neutralize the free acid to pH=6, and water is added to dilute the sodium diethylphosphinate to a mass concentration of 20%, and 0.02% (the amount added is calculated based on the weight of the diluted sodium diethylphosphinate aqueous solution) of lauryl ether alcohol phosphate is added, and 1 / 6 equivalent (calculated based on the molar amount of sodium diethylphosphinate) of a 20% aluminum sulfate aqueous solution is dripped at 35°C for 40 minutes; the temperature is raised to 55°C, and the remaining 5 / 6 equivalent (calculated based on the molar amount of sodium diethylphosphinate) of a 20% aluminum sulfate aqueous solution is dripped for 30 minutes; and the mixture is cooled and filtered in sequence, and the filter cake is washed three times with water three times the weight of the filter cake, and then dried at 120°C to constant weight to obtain a polymer additive.

[0075] Example 3 A polymer additive The difference between this embodiment and embodiment 1 is that: (2) The aqueous solution containing sodium diethylphosphinate obtained in step (1) is added with 20wt% sodium hydroxide aqueous solution to neutralize the free acid to pH=6, and water is added to dilute the sodium diethylphosphinate to a mass concentration of 20%, and 0.04% (the amount added is calculated based on the weight of the diluted sodium diethylphosphinate aqueous solution) of lauryl ether alcohol phosphate is added, and 1 / 3 equivalent (calculated based on the molar amount of sodium diethylphosphinate) of a 20% aluminum sulfate aqueous solution is dripped at 35°C for 40 minutes; the temperature is raised to 55°C, and the remaining 2 / 3 equivalent (calculated based on the molar amount of sodium diethylphosphinate) of a 20% aluminum sulfate aqueous solution is dripped for 20 minutes; and the mixture is cooled and filtered in sequence, and the filter cake is washed three times with water of three times the weight of the filter cake, and then dried at 120°C to constant weight to obtain a polymer additive.

[0076] Example 4 A polymer additive The difference between this embodiment and embodiment 2 is that: (2) The aqueous solution containing sodium diethylphosphinate obtained in step (1) is added with 20wt% aqueous sodium hydroxide solution to neutralize the free acid to pH=6, and water is added to dilute the sodium diethylphosphinate to a mass concentration of 22%, and 0.05% (the amount added is calculated based on the weight of the diluted sodium diethylphosphinate aqueous solution) of potassium lauryl phosphate is added, and 1 equivalent (calculated based on the molar amount of sodium diethylphosphinate) of a 22% aqueous aluminum sulfate solution is dripped at 30°C, and the temperature is slowly raised to 60°C at a heating rate of 4°C / 10 minutes, and the total dripping time is 100 minutes; then cooling and filtering are performed in sequence, and the filter cake is washed three times with water three times the weight of the filter cake, and then dried at 120°C to constant weight to obtain a polymer additive.

[0077] Example 5 A polymer additive (1) 396 kg of 50% phosphinic acid aqueous solution was put into an autoclave, 0.6 MPa nitrogen was used to replace the air in the autoclave for 5 times, ethylene was added until the ethylene pressure in the autoclave was 1.0 MPa, and the autoclave was heated to 80°C with stirring, and kept warm for 3 hours. 40 g of 10% sodium persulfate aqueous solution was continuously added during the 2-hour heat preservation process; during the heat preservation process, the material was pumped into the liquid inlet of the venturi ejector through a centrifugal pump from the bottom valve of the autoclave and the ethylene gas in the upper layer of the reactor entered from the gas inlet of the venturi ejector, and the gas and liquid phases were fully mixed and circulated into the reactor; ethylene entered from the gas inlet of the venturi ejector to supplement the ethylene consumed in the reaction to maintain the reactor pressure stable at 1.0 MPa. After the initiator was added, the autoclave was kept warm for 1 hour, cooled and vented to obtain an aqueous solution containing diethylphosphinic acid.

[0078] (2) At 20° C., 60 g of sodium hydroxide and 1140 g of water were used to prepare a sodium hydroxide aqueous solution, and the sodium hydroxide aqueous solution was slowly dripped into an aluminum sulfate aqueous solution prepared by 333 g of aluminum sulfate 18hydrate and 777 g of water over a period of 1.5 hours to obtain an aluminum hydroxide gel solution.

[0079] (3) The aluminum hydroxide gel solution was continuously dripped into an aqueous solution containing diethylphosphinic acid (the molar ratio of diethylphosphinic acid to aluminum ion was 3:1) within 3 hours, and then the temperature was increased to 60°C at a heating rate of 5°C / h, and kept at this temperature for 0.5 hours. The temperature was then increased to 100°C at a heating rate of 20°C / h, and kept at this temperature for 0.5 hours. The solution was then cooled and filtered in sequence. The filter cake was washed three times with water in an amount three times the weight of the filter cake, and then dried at 120°C to constant weight to obtain a polymer additive.

[0080] Example 6 A polymer additive The difference between this embodiment and embodiment 5 is that: (2) At 10°C, 60 g of sodium hydroxide and 1140 g of water were used to prepare a sodium hydroxide aqueous solution, which was slowly dripped into an aluminum sulfate aqueous solution prepared by 333 g of aluminum sulfate 18hydrate and 777 g of water over a period of 1.5 hours to obtain an aluminum hydroxide gel solution.

[0081] (3) The aluminum hydroxide gel solution was continuously dripped into an aqueous solution containing diethylphosphinic acid (the molar ratio of diethylphosphinic acid to aluminum ion was 3:1) within 3 hours, and then the temperature was increased to 60°C at a heating rate of 10°C / h, and kept at this temperature for 0.5 hours. The temperature was then increased to 100°C at a heating rate of 20°C / h, and kept at this temperature for 0.5 hours. The mixture was then cooled and filtered in sequence. The filter cake was washed three times with water in an amount three times the weight of the filter cake, and then dried at 120°C to constant weight to obtain a polymer additive.

[0082] Comparative Example 1 The existing polymer additive 1, XHPFR-1040, Zhejiang Xinhua Chemical Industry Co., Ltd. was used.

[0083] Comparative Example 2 The existing polymer additive 2, ADP-30, Lanzhou Ruipu Technology Co., Ltd. was used.

[0084] Test Case (1) The polymer additives prepared in Examples 1 to 6 and the polymer additives in Comparative Examples 1 to 2 were dissolved in a sodium hydroxide deuterated aqueous solution and their nuclear magnetic phosphorus spectra were tested.

[0085] (1) Instrument: Nuclear magnetic resonance spectrometer (Bruker 400M).

[0086] (2) Reagents: 10 wt% sodium hydroxide deuterated aqueous solution.

[0087] (3) Experimental method: Weigh about 0.1 g (accurate to 0.0001 g) of the sample to be tested, add 5 g of sodium hydroxide deuterated aqueous solution, and dissolve it by ultrasonication; transfer it to a nuclear magnetic resonance tube, and then place the nuclear magnetic resonance tube in a nuclear magnetic resonance analyzer to scan it to obtain a nuclear magnetic resonance spectrum. Integrate the diethylaluminum phosphinate and ethylbutylaluminum phosphinate in the nuclear magnetic resonance spectrum to obtain the molar percentage of the two, and after conversion, obtain the mass percentage of the two.

[0088] The test results of the polymer additives are shown in Table 1 below, in terms of mass percentage.

[0089] Table 1

[0090] (2) The polymer additives prepared in Examples 1 to 6 and the polymer additives in Comparative Examples 1 to 2 were tested by differential scanning calorimetry (DSC 214, NETZSCH DSC 204 F1, Germany) as follows: in a nitrogen atmosphere, the polymer additive was heated from room temperature to a maximum temperature of 300°C at a heating rate of 20°C / min, then kept at this temperature for 3 min and then cooled to room temperature at a rate of 20°C / min, to obtain a cooling curve of the polymer additive; the polymer additive was kept at room temperature for 3 min and then heated again to a maximum temperature of 300°C at a heating rate of 20°C / min, to obtain a second heating curve of the polymer additive.

[0091] Wherein, H1 is the peak area formed by the starting temperature and the ending temperature of the exothermic peak of the cooling curve; two endothermic peaks on the second heating curve are selected, and the temperature is from low to high, H2 is the peak area formed by the starting temperature and the ending temperature of the first endothermic peak on the second heating curve, and H3 is the peak area formed by the starting temperature and the ending temperature of the second endothermic peak on the second heating curve; In Table 2 below, ΔH = (H2 + H3) / H1; T1 is the peak temperature of the exothermic peak on the cooling curve, T2 is the peak temperature of the first endothermic peak on the second heating curve, and T3 is the peak temperature of the second endothermic peak on the second heating curve.

[0092] The peak temperature and peak area are obtained by calibration or calculation using the software provided in NETZSCH DSC 204 F1.

[0093] The test data of the polymer additives of Examples 1 to 6 and Comparative Examples 1 to 2 are shown in Table 2 below.

[0094] Table 2

[0095] (3) The polymer additives of Examples 1 to 6 and Comparative Examples 1 to 2 were used as flame retardants and were blended and extruded with a synergist, glass fiber, and a base resin to obtain a polymer molding material. The amounts of the components in Examples 7 to 16 and Comparative Examples 3 to 5 were shown in Table 3 in parts by weight.

[0096] Table 3

[0097] The molding shrinkage of the polymer molding materials prepared in the above Examples 7 to 16 and Comparative Examples 3 to 5 was tested using the test method in accordance with GB / T 15585-1995, and the shrinkage after 48 hours was measured. The test results are shown in Table 4 below.

[0098] Table 4

[0099] It can be seen from the data of the embodiment that the polymer molding material added with the polymer additive has a lower molding shrinkage during the molding application process. The transverse shrinkage of the polymer molding material added with the polymer additive is ≤0.81%, and the longitudinal shrinkage is ≤0.29%.

[0100] It can be seen from Examples 7, 13 and 14 that different synergists can be used in polymer molding materials to achieve good molding shrinkage. It can be seen from Examples 7, 15 and 16 that different base resins can be used to prepare polymer molding materials to achieve good molding shrinkage.

[0101] It can be seen from the examples, comparative examples 3 and 4 that when the double enthalpy ratio ΔH of the polymer additive, and T1, T2, T3 are within a specific range, the transverse shrinkage and longitudinal shrinkage of the polymer molding material to which the polymer additive is added are significantly reduced.

[0102] The foregoing embodiments are merely illustrative and are used to explain some features of the method of the present invention. The appended claims are intended to require the widest possible range that can be imagined, and the embodiments presented herein are demonstrated by the applicant's actual test results. Therefore, the applicant's intention is that the appended claims are not limited by the selection of examples that illustrate the features of the present invention. Some numerical ranges used in the claims also include sub-ranges within them, and changes in these ranges should also be interpreted as being covered by the appended claims where possible.

Claims

1. A polymer additive, characterized in that include: Aluminum diethylphosphinate and aluminum ethylbutylphosphinate; The polymer additive satisfies the double enthalpy ratio ΔH defined by the following formula (1): 0.90≤ΔH≤1.05; and satisfies 135°C≤T1≤160°C, 165°C≤T2≤185°C, 180°C≤T3≤200°C; Formula (1) ΔH = (H2 + H3) / H1; The polymer additive is tested by differential scanning calorimetry (DSC), and the testing method is as follows: in a nitrogen atmosphere, the polymer additive is heated from room temperature to a maximum temperature of 300°C at a heating rate of 20°C / min, and then cooled to room temperature at a rate of 20°C / min after staying at this temperature for 3 minutes, to obtain a cooling curve of the polymer additive; the polymer additive is kept at room temperature for 3 minutes, and then heated to a maximum temperature of 300°C at a heating rate of 20°C / min again, to obtain a second heating curve of the polymer additive; H1 is the peak area formed by the starting temperature and the ending temperature of the exothermic peak on the cooling curve; two endothermic peaks on the second heating curve are selected, and the temperature is from low to high, H2 is the peak area formed by the starting temperature and the ending temperature of the first endothermic peak on the second heating curve, and H3 is the peak area formed by the starting temperature and the ending temperature of the second endothermic peak on the second heating curve; T1 is the peak temperature of the exothermic peak on the cooling curve, T2 is the peak temperature of the first endothermic peak on the second heating curve, and T3 is the peak temperature of the second endothermic peak on the second heating curve.

2. The polymer additive according to claim 1, characterized in that: In terms of weight percentage, the polymer additive comprises: 99.01-99.99% of aluminum diethylphosphinate and 0.01-0.99% of aluminum ethylbutylphosphinate.

3. The polymer additive according to claim 1, characterized in that: Aluminum diethylphosphinate and aluminum ethylbutylphosphinate are present in a physical combination; and / or Aluminum diethylphosphinate and aluminum ethylbutylphosphinate are present in the form of chemical coprecipitation of ions of formula I and formula II; 。 4. The polymer additive according to claim 1, characterized in that: The polymer additive satisfies a double enthalpy ratio ΔH: 0.92≤ΔH≤1.

05.

5. The polymer additive according to claim 1 or 4, characterized in that: The polymer additive satisfies 140°C≤T1≤156°C, 172°C≤T2≤178°C, and 184°C≤T3≤192°C.

6. The method for preparing the polymer additive according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. Under nitrogen protection, a water-soluble salt or acid of hypophosphorous acid, an initiator and an olefin are reacted, and 2.00 to 2.05 molecules of olefin are added relative to the P of each water-soluble salt or acid of hypophosphorous acid itself to obtain an aqueous intermediate solution containing diethylphosphinate; S2. The intermediate aqueous solution of step S1, the surfactant and the aluminum salt solution are reacted to obtain the polymer additive.

7. The preparation method according to claim 6, characterized in that: In the step S1, the reaction temperature is 80-120°C.

8. The preparation method according to claim 6, characterized in that: In the step S1, the reaction pressure is 0.6-2.0 MPa.

9. The preparation method according to claim 6, characterized in that: In the step S2, the mass concentration of diethylphosphinate in the intermediate aqueous solution is 15-25%; in the step S2, the mass concentration of water-soluble aluminum salt in the aluminum salt solution is 20-24%.

10. The preparation method according to claim 6, characterized in that: In the step S2, the surfactant is selected from one or more of alkyl phosphate esters, alkyl phosphate salts, ether alcohol phosphate esters, and ether alcohol phosphate salts.

11. The preparation method according to claim 6, characterized in that: In step S2, the aluminum salt solution is added at one time, the temperature is raised to 50-60° C. during the addition process, and the addition time is controlled to be 90-110 min; or In step S2, aluminum salt solution is added twice. The first time, 15-35% equivalent aluminum salt solution is added, the addition time is controlled to be 30-40 minutes, and the temperature is controlled to be 35-45°C; the second time, 65-85% equivalent aluminum salt solution is added, the addition time is controlled to be 30-40 minutes, and the temperature is controlled to be 55-60°C.

12. The method for preparing the polymer additive according to any one of claims 1 to 5, characterized in that: The method comprises the following preparation steps: S1. Under nitrogen protection, an aqueous solution of hypophosphorous acid, an initiator and an olefin are reacted, and 2.00 to 2.05 molecules of olefin are added relative to the P of each hypophosphorous acid itself to obtain an aqueous intermediate solution containing diethylphosphinic acid; S2. Preparing an aluminum hydroxide gel solution; S3. The intermediate aqueous solution of step S1 is added dropwise to the aluminum hydroxide gel solution of step S2 for reaction, and the temperature is raised to 50-60°C and kept for 0.1-0.5h; the temperature is then raised to 90-120°C and kept for 0.5-5h to obtain a polymer additive.

13. Use of the polymer additive according to any one of claims 1 to 5 for reducing the shrinkage of a polymer.

14. Use of the polymer additive according to any one of claims 1 to 5 as a reactive and / or non-reactive flame retardant for polymers, as a flame retardant for varnishes and foaming coatings, as a flame retardant for wood and other cellulose-containing products, for the preparation of flame-retardant polymer molding materials, for the preparation of flame-retardant polymer moldings and / or for imparting flame retardancy to polyester and pure and blended cellulose fabrics by impregnation.

15. The use according to claim 14, characterized in that: The polymer additive is used together with a synergist; the synergist is melamine phosphate, melamine pyrophosphate, melamine polyphosphate, melamine and / or melamine cyanurate; it is a nitrogen-containing phosphate of the formula (NH4)yH3-yPO4 or (NH4PO3)z, wherein y is 1 to 3 and z is 1 to 10000; it is aluminum phosphite, aluminum pyrophosphite; it is zinc borate, zinc carbonate, zinc stannate, basic zinc stannate, zinc phosphate, zinc oxide, zinc hydroxide, tin oxide hydrate, basic zinc silicate, magnesium hydroxide, hydrotalcite, magnesium carbonate; it is a salt of ethylphosphonic acid, a salt of butylphosphonic acid, a salt of n-butylphosphonic acid, a salt of sec-butylphosphonic acid and / or a salt of hexylphosphonic acid.

16. The use according to claim 14, characterized in that: The polymer additive is used together with an additive selected from at least one of antioxidants, UV stabilizers, gamma ray stabilizers, hydrolysis stabilizers, antistatic agents, emulsifiers, nucleating agents, softeners, processing aids, impact modifiers, dyes or pigments.

17. The use according to claim 16, characterized in that: 0.0001-99.7999 wt% of the polymer additive, 0.1-40 wt% of the synergist and 0.1-40 wt% of the additive are used.

18. Flame-retardant thermoplastic or thermosetting polymer molding material, polymer molding, polymer film, polymer filament and / or polymer fiber, characterized in that The invention comprises: 0.5 to 45 wt % of the polymer additive according to any one of claims 1 to 5, 0.5 to 95 wt % of a thermoplastic or thermosetting polymer or a mixture thereof, 0 to 55 wt % of a synergist and 0 to 55 wt % of a filler or a reinforcing material.

19. The flame-retardant thermoplastic or thermosetting polymer molding material, polymer molding, polymer film, polymer filament and / or polymer fiber according to claim 18, characterized in that The polymer is selected from polyesters, polyamides, thermoplastic elastomers, thermoplastic polyurethanes, thermoplastic polyester elastomers, styrenic polymers, polyketones, polyolefins, polyacrylates and / or polymer blends comprising polyamides or polyesters.

Citation Information

Patent Citations

  • Preparation method and application of aluminum monotrifluoropropylphosphinate flame retardant

    CN110407869A

  • Nylon heat insulation strip material or reinforced nylon and glass fiber reinforced PA6 / PA66 composite material

    CN113637193A

  • Mixtures of flame protection means containing flame protection means and aluminium phosphites, method for production and use thereof

    CN104364305A

  • Preparation method and application of large-particle-size spherical dialkylphosphinate

    CN106632464A

  • Phosphorus-containing aluminum salt complex as well as preparation method and application thereof

    CN114539621A

Cited By

  • Polyamide composite material and application thereof

    CN120040966A